2008
DOI: 10.1021/ie071506u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Size, Applied Compression, and Substratum Material on Particle−Surface Adhesion Force Using the Centrifuge Technique

Abstract: The centrifuge technique was used to investigate the influence of particle size, applied compression, and substrate material (stainless steel, glass, Teflon, and poly(vinyl chloride)) on particle-surface adhesion force. For this purpose, phosphatic rock (F p ) 3090 kg/m 3 ) and manioc starch particles (F p ) 1480 kg/m 3 ) were used as test particles. A microcentrifuge that reached a maximum rotation speed of 14 000 rpm and which contained specially designed centrifuge tubes was used in the adhesion force measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…The Weibull and log-normal distributions were further validated in the study by Li et al (2006) which measured the adhesion forces between alumina particles and silica substrates with different coatings. Lognormal distributions were also found in a number of other experimental studies (Lam and Newton, 1992;Louey et al, 2001;Salazar-Banda et al, 2007;Felicetti et al, 2008) involving surfaces with significant roughness. Perni (2010, 2011) numerically and experimentally showed that the adhesion forces between PBT particles and glass and silicone surfaces follow a Gaussian distribution.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…The Weibull and log-normal distributions were further validated in the study by Li et al (2006) which measured the adhesion forces between alumina particles and silica substrates with different coatings. Lognormal distributions were also found in a number of other experimental studies (Lam and Newton, 1992;Louey et al, 2001;Salazar-Banda et al, 2007;Felicetti et al, 2008) involving surfaces with significant roughness. Perni (2010, 2011) numerically and experimentally showed that the adhesion forces between PBT particles and glass and silicone surfaces follow a Gaussian distribution.…”
Section: Methodsmentioning
confidence: 62%
“…The Kolmogorov-Smirnov (KS) test is conducted to rank the goodness-of-fit of the three distributions and the rankings are shown in Table 2. The modelled adhesion force distributions have the parameters in the range of experimentally measured ones by the existing studies (e.g., Lam and Newton (1992), Louey et al (2001), SalazarBanda et al (2007), and Felicetti et al (2008)). It is shown in Table 2 that the theoretical data of adhesion forces is best represented by log-normal distributions as indicated by the KS statistics, which measure the maximum vertical differences between the cumulative distribution functions of the theoretical models and the actual data.…”
Section: Model Validationmentioning
confidence: 99%
“…Then, the drum rotor was capped and the centrifuge was switched on to the designated rotational speed for 2 minutes. The duration of 2 minutes is used because the study of Felicetti et al [67] suggested that a longer duration had no effect on the observed adhesion force from the centrifuge experiments.…”
Section: Centrifuge Methodsmentioning
confidence: 99%
“…Apart from the inherent limitations as discussed above, the application of the mean adhesion force models is also limited due to the fact that the actual adhesion force between particles and a surface generally follows a distribution rather than a single value [50,[67][68][69][70][71][72][73][74][75][76][77]. Therefore, solely understanding the mean adhesion force is not enough for accurate depiction of the actual particle-surface adhesion relevant phenomena (e.g., particle resuspension).…”
Section: Mean Adhesion Force Modelmentioning
confidence: 99%
See 1 more Smart Citation